The Study Of Leader Member Exchange (LMX) And Team Member Exchange(TMX) - Nian, Foong Hong (2009)
This study assess the associated affect of leader-member exchange and other contextual variables such as Perceived Organization Support (POS), Organization Citizenship Behavior (OCB), Supervisor-Subordinate Communication, Team Member Exchange, Trust Context, job satisfaction, fairness perceptions and others.